THE ANALYSIS OF ENGLISH EDUCATION STUDENTS' DIFFICULTIES IN PRONOUNCING ENGLISH VOWELS - Dwi Yulianti; Qoeddri Farhansyah; Yani Lubis (Cendekia Madani Nusantara, 2024)
The purpose of this study was to identify the difficulties faced by ELT students in pronunciating English vowels, especially those that are not pronounced correctly and consistently. The subjects of this research are English language education students. The study adopted a descriptive qualitative and then utilized observation and video recording techniques to observe and analyze students' pronunciation of English vowel words. Results indicate that there were 11 words mispronounced by students with a percentage of 50% of the word langgon, 17% of the word early, 8.3% of the word catch, 33% of the word ligament, 17% of the word fork, 17% of the word yeast, 8.3% of the word lake, 8.3% of the word harm. 8.3%, the word suffer 8.3%, and the word fool 8.3%. The data shows that students often have difficulty pronouncing vowels correctly. The study also highlights the influence of a student's native language on the pronunciation of English vowels and the importance of understanding phonetic symbols for accurate pronunciation. Based on these findings, the study suggests that ELT students should be provided with additional resources and support to improve their pronunciation skills, particularly in the area of vowels. The study also highlights the influence of a student's native language on the pronunciation of English vowels and the importance of understanding phonetic symbols for accurate pronunciation. Based on these findings, the study suggests that ELT students should be provided with additional resources and support to improve their pronunciation skills, particularly in the area of ​​vowels.